STUDI KASUS KETERAMPILAN SOSIAL: KOMUNIKASI SISWA DALAM PEMBELAJARAN KOOPERATIF DAN KOLABORATIF - Nabila, Dima Syafa’a; Handayanto, Supriyono Koes; Susilo, Wahyu Hadi (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2024)
Abstract: This study examines the differences in students' communication skills between cooperative and collaborative learning at SMPN 24 Malang, Indonesia. The study uses a qualitative method with a case study approach to explore how students' communication skills are manifested in real learning situations. Data were collected through in-depth interviews and direct observation, then analyzed using a descriptive qualitative method. The findings indicate that students in collaborative learning tend to be more open and active in communication, while those in cooperative learning are more passive and experience limitations in communication skills. Factors influencing communication skills include self-confidence, motivation, personal relationships, and perceptions of other group members. The study suggests that teachers should alternate between cooperative and collaborative approaches and assist students in overcoming negative perceptions that may hinder communication skills within the group